Design and Control of a Fabric Vacuum-Powered Artificial Muscle for Rehabilitation Devices - Cancán, Sergio; Vela, Emir A. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
Cerebral palsy (CP) is a group of disorders affecting a baby’s motor functions, such as walking, balance, and posture. It is the most common childhood disability, with a reported prevalence of 5.2 per 1,000 newborns in Peru, approximately double the global rate. Conventional treatment for cerebral palsy, crucial due to potential growth complications, primarily involves physical therapy. The availability of therapies is limited by factors such as the shortage of specialists and their uneven distribution across Peru. Therefore, developing a flexible robotic rehabilitation device is necessary to expand access to rehabilitation for more patients. This article proposes an artificial muscle integrated into a rehabilitation device focused on hip flexion and extension movements, featuring lower hysteresis to improve controllability.. The device effectively performs rehabilitation movements with a steady-state error of less than 2.5% using a PID controller, with all tests conducted on a 6-month-old infant mannequin.